The Global Technology Revolution 2020, In-Depth Analyses: Bio/Nano/Materials/Information Trends, Drivers, Barriers, and Social Implications - Silberglitt, Richard (RAND Corporation, 2006)
In 2020, areas of particular importance for technology trends will include biotechnology, nanotechnology, materials technology, and information technology. This report, the companion document to The Global Technology Revolution 2020, Executive Summary (Silberglitt et al., MG-475-NIC, 2006), assesses in detail a sample of 29 countries with respect to their ability to acquire and implement 16 key technology applications.